Influence of typical street-side public building morphologies on the ventilation performance of streets and squares. (1st August 2022) - Xu, Fusuo; Gao, Zhi; Zhang, Jianshun; Hu, Yongyu; Ding, Wowo
Abstract: The deterioration of the urban environment has captured the attention of governmental departments and research institutions, which aim to improve the urban environment from the perspective of optimizing urban morphology. Although ideal building arrays and residential building morphologies have been previously studied, research on the relationship between public building morphology and urban ventilation is currently scarce. Therefore, we used computational fluid dynamics (CFD) to analyze the relationship between six public building morphologies extracted from real cities and urban ventilation. This study bridges the gap between public building morphology and urban ventilation and guides the future architectural design and urban planning. The purging flow rate and age of air were used to quantify the ventilation capacity of the squares, paths, and streets in public building blocks. The results show that a square space formed by public building setbacks can form a broad space with a path and street, which is conducive to incoming wind, resulting in better ventilation capacity. Overall, public building morphologies with 8 m street-side setbacks and 16 m path-side setbacks exhibited higher superiority rates for both single and multiple public building morphologies (66.7% and 83.3%, respectively). This study concluded that a public building morphology with 8 m street-side setbacks is the best because of a high ventilation capacity (total superiority rate = 66.7%) and building packing density. Highlights: Six typical public building morphologies were categorized based on the real city. Age of air and purging flow rate were used to analyze outdoor ventilation. The ventilation capacity of the square, path, and street spaces was evaluated. Morphology with 16 m path-side setbacks has the highest superiority rate (83.3%). 8 m street-side setbacks form is suggested due to ventilation and floor area ratio.